Transformational School Principal Leadership Behavior and Its Impact on School Climate - Edward Leroy Myers (Arizona State University, 2014)
During the last two decades, researchers and theorists have offered a variety of conceptual designs and empirical findings regarding school leadership conduct, as it relates to organizational climate concerns. As a supplement to the literature, this paper will examine the intentions, decisions, behaviors, and school outcomes associated with one senior high school principal who endeavored to recreate his school organization. The purpose of this paper is to further the understanding of how transformational leadership manifests in the school organization, and to determine how it impacts school climate. The studys findings may be beneficial for school leaders and scholars who wish to better understand the school transformation process.